Nutritional quality of dry feeds from different commercial segments for dogs (Research, Society and Development, 2020)
The objective was to determine the chemical composition of dry dog food by comparing the results analyzed with the information declared on their respective labels. 21 complete foods for dogs were purchased in feed houses and pet shops in the city of São João del Rei in order to assess the nutritional composition, 15 for adult dogs and six for puppies, manufactured by 14 different companies. Bromatological analyzes were performed to determine the levels of crude protein (CP), ether extract (EE), mineral matter (MM), dry matter (DM) and crude fiber (CF). The maximum humidity guarantee levels proved to be 100% within the standards in all commercial segments. However, MM levels resulted in 85.7%; 57.1% and 100% within the standards for the Standard, Premium and Super premium segments respectively. For CP the results were 100% compliance, for Super premium and 71.4% compliance for Standard and Premium. The results of EE compared to the values observed on the labels, were Standard with 71.4%, Premium 54.1% and Super premium with only 28.5% of compliance. Finally, for CF, 85.7% of the Standard samples and also, the same value for Premium were shown within the comparison standards label / analyzes. It can be concluded that dry dog food for puppies and adults meets most of the maximum and minimum limits required by MAPA. However, there is a deficiency in the labeling in relation to the information provided of the guarantee levels, which can lead consumers to error when choosing the ration.